Effect of nickel, cobalt, and iron on methanogenesis from methanol and cometabolic conversion of 1, 2‐dichloroethene by Methanosarcina barkeri. (12th May 2020) - Paulo, Lara M.; Hidayat, Mohamad R.; Moretti, Giulio; Stams, Alfons J. M.; Sousa, Diana Z.
Abstract: Methanogens are responsible for the last step in anaerobic digestion (AD), in which methane (a biofuel) is produced. Some methanogens can cometabolize chlorinated pollutants, contributing for their removal during AD. Methanogenic cofactors involved in cometabolic reductive dechlorination, such as F430 and cobalamin, contain metal ions (nickel, cobalt, iron) in their structure. We hypothesized that the supplementation of trace metals could improve methane production and the cometabolic dechlorination of 1, 2‐dichloroethene (DCE) by pure cultures of Methanosarcina barkeri . Nickel, cobalt, and iron were added to cultures of M. barkeri growing on methanol and methanol plus DCE. Metal amendment improved DCE dechlorination to vinyl chloride (VC): assays with 20 µM of Fe 3+ showed the highest final concentration of VC (5× higher than in controls without Fe 3+ ), but also in assays with 5.5 µM of Co 2+ and 5 µM of Ni 2+ VC formation was improved (3.5–4× higher than in controls without the respective metals). Dosing of metals could be useful to improve anaerobic removal of chlorinated compounds, and more importantly decrease the detrimental effect of DCE on methane production in anaerobic digesters. Abstract : Methanosarcina barkeri (DSM800 T ) is able to cometabolically reduce 1, 2‐dichloroethene (DCE) to vinyl chloride (VC) with methanol as electron donor. However, the presence of DCE inhibits methane production by this organism. In this study, we evaluate if the supplementation of cobalt, nickel, and iron (required for methanogenic activity and reductive dechlorination) can improve methane production by M. barkeri in the presence of DCE.